Comparison of training responses and performance adaptations in endurance-trained men and women performing high-intensity interval training - Hoffmann, S.; Skinner, T. L.; van Rosendal, S. P.; Emmerton, L. M.; Jenkins, D. G. (Journal of Sports Sciences, 2021)
The efficacy of high-intensity interval training (HIIT) to elicit physiological and performance adaptations in endurance athletes has been established in men and to a lesser extent in women. This study compared lactate threshold (LT2) and performance adaptations to HIIT between men and women. Nine male and eight female cyclists and triathletes completed trials to determine their LT2 and 40 km cycling performance before, and after 10 HIIT sessions. Each HIIT session consisted of 10 × 90 s at peak power output, separated by 60 s active recovery. Main effects showed that HIIT improved peak power output (p = 0.05; ES: 0.2); relative peak power output (W.kg-1; p = 0.04; ES: 0.3 and W.kg-0.32; p = 0.04; ES: 0.3); incremental time to fatigue (p = 0.01; ES: 0.4), time trial time (p < 0.001; ES: 0.7) and time trial power output (p < 0.001; ES: 0.7) equally in both sexes. Although LT2 power output explained 77% of the performance improvement in women, no variable explained the performance improvement in men, suggesting another mechanism(s) was involved. Although HIIT improved cycling performance in men and women, it might not be appropriate to evaluate the effectiveness of HIIT using the same variables for both sexes.